Aerodynamic investigations of ventilated brake discs. - Parish, D.; MacManus, David G. (Professional Engineering Publishing, 2005)
The heat dissipation and performance of a ventilated brake disc strongly depends on the aerodynamic characteristics of the flow through the rotor passages. The aim of this investigation was to provide an improved understanding of ventilated brake rotor flow phenomena, with a view to improving heat dissipation, as well as providing a measurement data set for validation of computational fluid dynamics methods. The flow fields at the exit of four different brake rotor geometries, rotated in free air, were measured using a five-hole pressure probe and a hot-wire anemometry system. The principal measurements were taken using two-component hot-wire techniques and were used to determine mean and unsteady flow characteristics at the exit of the brake rotors. Using phase-locked data processing, it was possible to reveal the spatial and temporal flow variation within individual rotor passages. The effects of disc geometry and rotational speed on the mean flow, passage turbulence intensity, and mass flow were determined. The rotor exit jet and wake flow were clearly observed as characterized by the passage geometry as well as definite regions of high and low turbulence. The aerodynamic flow characteristics were found to be reasonably independent of rotational speed but highly dependent upon rotor geometry.
Keywords: brake disc; ventilated; aerodynamics; heat transfer; unsteady flow; turbulence